The Calculation of Ni-Sn-W Alloy Phase Diagram Using CALPHAD Method As New Soldering Material - Riswan Eko Susanto; Gita Novian Hermana (Universitas Trunojoyo Madura, 2019)
The Ni-Sn-W Alloy becomes an alternative as the Ni element could slow and block the forming of intermetalic. Beside, the existence of the W element could add the solder materials performance which is able to block the forming of intermetalic substance. Calculation of phase diagram (CALPHAD) is able to become a solution for the limited information about phase diagram whether two system (biner) or others systems above. Computing method of CALPHAD used the factual approach and assumed that it is the characteristic of thermodynamic. From the calculation, the result gained are Ni3Sn, Ni3Sn2, Ni3Sn4, solidus Sn (Sn), solidus Ni (Ni), NiW, Ni4W, solidus W (W), and solidus liquid (L).